Penyuluhan Hukum Perdata dan Pidana Bagi Aparat Kelurahan - Lira, Adnan (ADPERTISI, 2023)
Legal development in Indonesia aims to achieve justice, truth, and order, but the complexity of the overlap between criminal law and civil law poses a challenge. Criminal law is regulated by the Criminal Code (KUHP) and often overlaps with civil law. Updating and harmonizing are needed for better legal clarity. Civil law, governing relationships between individuals, is crucial in civic education. Public and government legal awareness influences legal effectiveness. Legal education needs to be improved nationally to achieve the goal of a legal state. Interactive and participatory legal education methods are used in this activity. Post-test results show a significant improvement in understanding among 169 participants, especially in procedural law. Legal education creates a positive dialogue environment and addresses the lack of knowledge among village officials. Although successful, follow-up in the form of advanced training is recommended to maintain and deepen participants' understanding of daily legal issues. In conclusion, this activity has a positive impact on the legal knowledge of village officials, but ongoing steps are needed for a deeper understanding of the legal aspects presented